Dynamics of Xavi Hernández`s game: A vectorial study through polar coordinate analysis - Maneiro, R.; Amatria, M.; Anguera, M. T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
The evolution of soccer over the past 30 years has brought about a faster pace of play and more demanding player dynamics that have led to a paradigm shift in how the game is analyzed. Classic, purely descriptive studies of midfielder performance paint a disjointed picture that is far from the reality of the complex network of relationships and interactions that mark modern-day soccer. The aim of this study was to investigate the relationships established by Xavier "Xavi" Hernández, captain of FC Barcelona and a member of the Spanish national team for many years, during his participation in the final stages of the 2012 UEFA European Football Championship. The authors studied Xavi`s relationship with other players on the pitch, the areas in which his interventions started and ended, his use of technical-tactical skills, and his involvement in set plays. A modified version of a purpose-designed observation instrument was used within an observational methodology study. The data were analyzed by polar coordinate analysis, which is a powerful data reduction technique that reveals significant prospective and retrospective relationships between a focal behavior (Xavi) and other behaviors of interest. The results show that Xavi presents a mutual activation with behaviors from J6 (Iniesta) and J21 (Silva) and significant relationships in attack set-up zones. He is also the most important player in set piece situations, when he uses technical behaviors of control and passing. Studies on tactical performance should analyze all inputs of play and focus on a deep, layered analysis of results to facilitate the work of soccer coaches and educators.